Production of cellulase by liquid state bioconversian of sewage treatment plant sludge - Afifah binti Drani (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Sewage treatment plant (STP) sludge is a very good source of carbon, nitrogen, phosphorus and other nutrients for many microbial processes which make it potentially interesting raw material source for enzyme production. Cellulases are important enzymes that are sold in large volumes for use in different industrial applications. This enzyme is produced by several microorganisms, commonly by bacteria and fungi. Filamentous fungus Trichoderma reesei is considered to be one of the most efficient hyper producers of cellulase that is widely used in industry. In this study, the utilization of STP sludge as main substrate for cellulase fermentation has been investigated. The study for production of cellulase from STP sludge through liquid state bioconversion (LSB) by filamentous fungus Trichoderma reesei Rut C-30 was conducted by several approaches. The main objective of the study was to formulate and develop bioconversion process for cellulase production by Trichoderma reesei Rut C-30 using STP sludge as major substrate. A statistical design method was employed to optimize the media constituents for cellulase production from sewage sludge through liquid state bioconversion (LSB) by filamentous fungus Trichoderma reesei Rut C-30. Media constituents with significant effects on cellulase production were identified using Plackett-Burman design and their levels were optimized using face centered central composite design to improve cellulase yield. The statistical analysis of experimental results showed that the optimum media constituent for cellulase production using sewage sludge as the basal medium, containing 1.5% cellulose and 0.5% peptone, supplemented with 0.25% KH2PO4, 0.2% tween 80, and 0.03% MgSO4 gave the maximum cellulase activity of 21.33 U/ml (CMCase activity). Process optimization result showed that the bioconversion conditions and inoculum dose highly influenced the cellulase production. Fractional factorial design was used to optimize process parameters and after statistical analysis of experimental result, optimum process conditions were found to be temperature 28oC, inoculum size 5% (v/v), pH 4.0, aeration 1.5 vvm and agitation 100 rpm. The highest cellulase production of 40.71 U/ml was obtained after five days of fermentation with optimum media constituents and process conditions in 30L stirred tank bioreactor. A scale-up study from 30L to 300L fermenter was carried out using tip speed and superficial velocity as the scale-up criterion in order to study the feasibility of commercial scale cellulase production from bioconversion of sewage sludge by Trichoderma reesei. Maximum enzyme activity attained were 2.17 FPU/ml of total cellulase activity, 48.52 U/ml of CMCase activity and 0.23 U/ml of β-glucosidase. This research work generally offers a potentially less expensive alternative in the cellulase production and contributes in the reduction of environmental pollution. Thus, this approach is economically valuable, non-hazardous and environmentally friendly.